2017
DOI: 10.1080/00224499.2017.1399195
|View full text |Cite
|
Sign up to set email alerts
|

Passion, Intimacy, and Commitment in Casual Sexual Relationships in a Canadian Sample of Emerging Adults

Abstract: Research on casual sexual relationships (CSRs) among emerging adults is prevalent, yet our empirical and theoretical knowledge of relationship processes involved in these relationships is limited. The present study's objective was to compare four CSR partner types (acquaintance, friend, non-dating partner, ex-romantic partner) on passion, intimacy, and commitment, the components of Sternberg's triangular theory of love. A total of 441 Canadians aged 18-25 years who were not in a romantic relationship, and who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 80 publications
4
7
0
1
Order By: Relevance
“…Sexual contact in the three scripts includes different sexual practices, which is in line with the literature that highlights significant levels of passion in different types of CSR (Rodrigue et al., 2018 ). However, the three scripts can be distinguished according to the pace of the development of the relationship toward sex and subjective experience of sex, likely related with the motivations each participant has in engaging in one of these relationships and the CSR partner.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…Sexual contact in the three scripts includes different sexual practices, which is in line with the literature that highlights significant levels of passion in different types of CSR (Rodrigue et al., 2018 ). However, the three scripts can be distinguished according to the pace of the development of the relationship toward sex and subjective experience of sex, likely related with the motivations each participant has in engaging in one of these relationships and the CSR partner.…”
Section: Methodssupporting
confidence: 80%
“…A less-expected finding, but one that is in line with the evidence of transitions occurring between different types of relationships (Hadden et al., 2019 ), is that this script includes the possibility of repeated encounters when partners enjoyed being together. This feature may indicate that, despite a lower emotional involvement in this CSR when compared to hookup and, especially, friends with benefits , the one-night stand is neither as straightforward nor as totally detached as its definition may suggest, endorsing the idea that being good sex partners may (emotionally) bond CSR partners (Rodrigue et al., 2018 ). This finding puts forward the possibility of a sexual encounter that more frequently associated with risky health and sexual behaviors (e.g., alcohol and substance use, unprotected sex with strangers) may also be a potential basis for sexual activities and expression that lead to enjoyment and (sexual) pleasure due to its free and spontaneous character – a finding that endorses the need to change the discourse around sexuality to include the beneficial aspects of sexuality (Ford et al., 2021 ; Gianotten et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This theory suggests that casual relationships differ in terms of intimacy, passion, and commitment. Previous studies have shown that casual sexual relationships are characterised by moderate (Bisson and Levine, 2009) to high (Rodrigue et al, 2018) levels of passion, low (Bisson and Levine, 2009) to moderate (Rodrigue et al, 2018) levels of intimacy, and low levels of commitment (Bisson and Levine, 2009). Our findings suggest that partners in casual sexual relationships such as one-night stands, booty calls, and fuck buddies experience high levels of passion and low levels of intimacy and commitment.…”
Section: Discussionsupporting
confidence: 54%
“…Casual sexual relationships were indeed characterised by high levels of passion, but also by medium levels of intimacy, which means that these relationships can indeed be described as romantic or infatuated types of love. While non-romantic partners, i.e., partners that are in love, but are not dating, engage in sexual activity more frequently than friends, friends engage socially more frequently than acquaintances (Rodrigue et al, 2018). Bisson and Levine (2009), on the other hand, found that friends involved in casual sexual relationships perceive moderate intimacy, as well as low passion and commitment.…”
Section: The Triangular Theory Of Lovementioning
confidence: 96%
“…Le recours a `un devis longitudinal sur cinq ans permet de mieux cerner la contribution des parents sur l'émergence de la sexualité dans le contexte amoureux a l'adolescence et d'en examiner l'évolution a `court terme. Enfin, les nouvelles tendances quant aux comportements des jeunes en matière de sexualité et aux partenaires occasionnels ont beaucoup retenu l'attention des chercheurs durant les dernières années (Dubé, Lavoie, Blais & Hébert, 2017;Rodrigue et al, 2018), délaissant l'aspect développemental et adaptatif des comportements sexuels dans un contexte amoureux. Ce faisant, les résultats rapportés ici amènent de nouvelles perspectives en ce qui concerne la dynamique relationnelle et le rôle des parents sur la santé sexuelle des jeunes.…”
Section: Forces Et Limitesunclassified